90Sr and 137Cs inventories in the depots and biogenic fluxes of the typical forest stands in the Chernobyl exclusion zone - D. M. Holiaka; S. E. Levchuk; V. I. Yoschenko; V. A. Kashparov; L. V. Yoschenko; M. A. Holiaka; V. V. Pavliuchenko; P. P. Diachuk; R. M. Zadorozhniuk; V. S. Morozova (Ядерна фізика та енергетика)
The paper reports results of the study of depots and biogenic fluxes of 90Sr and 137Cs in the typical coniferous (Scots pine) and deciduous (Silver birch) forest ecosystems of the Chernobyl Exclusion Zone during 2016 - 2018. Data on activity concentrations and shares of the total activity of the studied radionuclides in the components of aboveground and underground biomass and their vertical distributions by 10 cm layers of the soil profile up to a depth of 1 m are presented. The downward and upward fluxes of 90Sr and 137Cs activity (including the processes of their deposition as a result of growth and formation biomass) are calculated in annual terms. Significantly higher 90Sr mobility in elements of forest ecosystems than 137Cs is confirmed. The estimated flux values for the investigated forest areas indicate a gradual further increase in the share of these radionuclides in the aboveground biomass components (up to 0.9 %·year-1 from the total activity in forest ecosystems) owing to the increase of organic matter stocks.